2001
DOI: 10.1007/s002130100688
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying drug-related 5-HT1A receptor occupancy with [18F]MPPF

Abstract: These results show that [18F]MPPF can be used for measurement of drug-related 5-HT1A receptor occupancy and may be of particular interest in determining the 5-HT1A receptor interaction of new or established drugs in phase 1 and early phase 2 drug trials. Apparently, the 5-HT1A partial agonist buspirone is already clinically effective at low levels of 5-HT1A receptor occupancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…Low levels of 5-HT 1A receptor occupancy by buspirone at clinically effective doses have been reported previously in human positron emission tomography studies (Rabiner et al, 2000;Passchier et al, 2001). A single dose of 10 or 40 mg of buspirone occupies ϳ5% 5-HT 1A receptors in healthy human subjects (Rabiner et al, 2000;Passchier et al, 2001).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Low levels of 5-HT 1A receptor occupancy by buspirone at clinically effective doses have been reported previously in human positron emission tomography studies (Rabiner et al, 2000;Passchier et al, 2001). A single dose of 10 or 40 mg of buspirone occupies ϳ5% 5-HT 1A receptors in healthy human subjects (Rabiner et al, 2000;Passchier et al, 2001).…”
Section: Discussionmentioning
confidence: 53%
“…A single dose of 10 or 40 mg of buspirone occupies ϳ5% 5-HT 1A receptors in healthy human subjects (Rabiner et al, 2000;Passchier et al, 2001). A similar low fraction (Ͻ10%) of occupancy in humans has been observed with other selective and nonselective 5-HT 1A agonists such as tandospirone, flesinoxan, and EMD 128 130 after single or multiple clinical doses capable of activating central 5-HT 1A receptor functions (Nakayama et al, 2002;Rabiner et al, 2002;Bantick et al, 2004).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…It is also of note that the pharmacodynamic effects of agonists binding to receptors can be considerable, even at low levels of occupancy, because of signal amplification. Therefore, although 5-HT 1A receptor occupancy with antagonists has been readily observed in animal and human PET studies, with occupancies as high as 52-71% in man with 40 mg DU 125530 (Rabiner et al, 2002c), agonist occupancy has only been identified in animal PET studies Shiue et al, 1997), and not in human studies (using lower drug doses) despite their pharmacological effects being manifest (Passchier et al, 2001;Nakayama et al, 2002;Rabiner et al, 2002a).…”
Section: Figurementioning
confidence: 96%
“…It can be assumed that only a limited portion of [ 11 C]WAY 100635 binding might be susceptible to tandospirone. Passchier et al (2001) also failed to find a measurable occupancy by a clinical dose of buspirone, a 5-HT 1A partial agonist, using the antagonist radioligand [ 18 F]MPPF. Another possible explanation is the spare receptor or receptor reserve hypothesis, which is based on the idea that in the systems with a large "receptor reserve" (Goldenstein et al 1974), ED 50 can be expected to be much less than the dose at 50% receptor occupancy (Furchgott 1978), and the pharmacological effect is acquired at a low occupancy.…”
Section: Discussionmentioning
confidence: 86%